2012
DOI: 10.3389/fncir.2012.00015
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon scanning microscopy of in vivo sensory responses of cortical neurons genetically encoded with a fluorescent voltage sensor in rat

Abstract: A fluorescent voltage sensor protein “Flare” was created from a Kv1.4 potassium channel with YFP situated to report voltage-induced conformational changes in vivo. The RNA virus Sindbis introduced Flare into neurons in the binocular region of visual cortex in rat. Injection sites were selected based on intrinsic optical imaging. Expression of Flare occurred in the cell bodies and dendritic processes. Neurons imaged in vivo using two-photon scanning microscopy typically revealed the soma best, discernable again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 77 publications
0
16
0
Order By: Relevance
“…Another study recently reported TPSM of Flare-reported cellular resolution signals in visual cortex35. However, the signals responding to visual stimuli were very weak, requiring extensive trial averaging (> 100), while lacking convincing validation to proof that these signals reliably represent membrane voltage, given that Flare and other first generation GEVIs, derived from voltage-gated ion channels, were not functional when tested in cultured mammalian cells45.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study recently reported TPSM of Flare-reported cellular resolution signals in visual cortex35. However, the signals responding to visual stimuli were very weak, requiring extensive trial averaging (> 100), while lacking convincing validation to proof that these signals reliably represent membrane voltage, given that Flare and other first generation GEVIs, derived from voltage-gated ion channels, were not functional when tested in cultured mammalian cells45.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, in-vitro studies recently demonstrated single-trial sensitivity for recording of action potentials in axonal terminal arbors32, back-propagated action potentials in single spines33 and spontaneous and evoked somatic potentials in neurons in acute brain slice34 using 2-photon imaging of voltage-sensitive dyes. On the other hand, available 2-photon imaging data of sensory-evoked activity in somatosensory and visual cortex remained poor in signal-to-noise requiring extensive trial averages (> 100) to surpass the noise levels3135.…”
mentioning
confidence: 99%
“…Interestingly, protein engineers have leveraged not one, but two distinct voltage sensing mechanisms for developing protein-based voltage sensors: voltage-sensitive conformational states, and voltage-sensitive photophysical states. These sensors are beginning to be used to capture neural voltage dynamics in vivo in a variety of model systems including worms [48••], flies [51•], and mammals [17-19,22,49••,52,53•,54,55]. Voltage sensors are also beginning to be used to monitor cardiac electrical activity in vitro [56] and in living zebrafish [57,58].…”
Section: Introductionmentioning
confidence: 99%
“…First, the ability to image electrical activity with two-photon laser scanning microscopy — an important technique for deeper tissue penetration and lower out-of-focus fluorescence — has been established for some sensors based on VSDs [53•,55] but not for opsin-based sensors. Second, to be a true replacement of electrodes, voltage indicators should be able to report absolute voltage, not only in vitro [59] but also in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose several voltagesensing proteins (e.g., FLaSh, VSFP2, SPARC, Flare, Opto-patch) have been designed that work well with 2PE microscopy and could in theory be useful to monitor the activity of thousands of individual neurons simultaneously [67][68][69]. These sensors are usually FRET based and can report both subthreshold changes in membrane potential and spiking activity of neurons.…”
Section: Calcium Imagingmentioning
confidence: 99%